Tropospheric ozone effects on chemical composition and decomposition rate of Quercus ilex L. leaves. - Baldantoni, Daniela; Fagnano, Massimo; Alfani, Anna (The Science of the total environment, 2011)
We determined the effects of tropospheric ozone on the chemical composition of Quercus ilex L. leaves and their decomposition, with a view to assessing the influence of ozone on nutrient cycling and the sustainability of Mediterranean holm oak forests. Forming one of the most widespread thermophilous vegetation communities in the area, Q. ilex is a dominant and widespread evergreen oak in the Mediterranean, where concentrations of tropospheric ozone are particularly high. The dynamics of carbon, nitrogen, lignin and cellulose concentrations were monitored for six months during the decomposition of leaves from plants subjected to controlled ozone exposure in open-top chambers. Ozone-exposed leaves, compared to unexposed leaves, showed no significant differences in C, N, lignin and cellulose concentrations prior to the incubation in mesocosms. However, during decomposition, leaves from plants exposed to ozone lost C significantly more slowly and showed a higher C/N ratio than unexposed leaves. Ozone exposure significantly slowed down the decomposition rate, indicating a negative effect of tropospheric ozone on nutrient cycling, which may reduce long-term sustainability of the holm oak forest.
Keywords: Air Pollutants; Air Pollutants: chemistry; Air Pollutants: metabolism; Air Pollutants: toxicity; Atmosphere; Atmosphere: chemistry; Carbon; carbon cycle; Carbon: analysis; Carbon: metabolism; Cellulose; Cellulose: analysis; Cellulose: metabolism; Decaying leaf composition; Holm oak leaves; Lignin; Lignin: analysis; Lignin: metabolism; Mediterranean area; nitrogen; nitrogen cycle; Nitrogen: analysis; Nitrogen: metabolism; Ozone; ozone exposure; Ozone: chemistry; Ozone: metabolism; Ozone: toxicity; Plant Leaves; Plant Leaves: chemistry; Plant Leaves: metabolism; Quercus; Quercus: chemistry; Quercus: metabolism

Microbial activity and quality changes during decomposition of Quercus ilex leaf litter in three Mediterranean woods - Papa, S.; Pellegrino, A.; Fioretto, A. (Applied Soil Ecology, 2008)
Changes in enzyme activities during litter decomposition provide diagnostic information on the dynamics of decay and functional microbial succession. Here we report a comparative study of enzyme activities involved in the breakdown of major plant components and of other key parameters (microbial respiration, fungal biomass, N, lignin and cellulose contents) in homogeneous leaf litter of Quercus ilex L. incubated in three evergreen oak woods in Southern Italy (Campania), differing for chemical and physical soil characteristics and microclimatic conditions. The results showed that the litter mass loss rates were similar in the three wood sites. Independently of the incubation sites, cellulase, xylanase and peroxydase activities showed seasonal variations with maximum and minimum levels in wet and dry periods, respectively, and this pattern closely matched microbial respiration. Activities of a- and b-amylase, instead, were high at the beginning of incubation and quickly decreased with decomposition progress because their substrate was rapidly depleted. Laccase activity, in contrast, was low at the beginning of incubation but after 6 months it increased signiﬁcantly. The increase of laccase activity was correlated to an increase in fungal biomass, probably reﬂecting a major shift in the litter microbial community. As concerns quality changes, N and lignin content did not signiﬁcantly change during decay. The cellulosic component started being degraded after about 6 months in the litter incubated in two of the three wood sites and from the start of decomposition in the third site. Apart from minor differences in the levels of certain enzyme activities, the data showed that the functional microbial succession involved in the decomposition of Q. ilex leaf litter did not change appreciably in response to differences in soil and microclimatic conditions in the incubation sites.
Keywords: Cellulose; Enzyme activities; Fungal biomass; Lignin; litter decomposition; Microbial respiration

Microbial activity and quality changes during decomposition of Quercus ilex leaf litter in three Mediterranean woods - Papa, S; Pellegrino, a; Fioretto, a (Applied Soil Ecology, 2008)
Changes in enzyme activities during litter decomposition provide diagnostic information on the dynamics of decay and functional microbial succession. Here we report a comparative study of enzyme activities involved in the breakdown of major plant components and of other key parameters (microbial respiration, fungal biomass, N, lignin and cellulose contents) in homogeneous leaf litter of Quercus ilex L. incubated in three evergreen oak woods in Southern Italy (Campania), differing for chemical and physical soil characteristics and microclimatic conditions. The results showed that the litter mass loss rates were similar in the three wood sites. Independently of the incubation sites, cellulase, xylanase and peroxydase activities showed seasonal variations with maximum and minimum levels in wet and dry periods, respectively, and this pattern closely matched microbial respiration. Activities of a- and b-amylase, instead, were high at the beginning of incubation and quickly decreased with decomposition progress because their substrate was rapidly depleted. Laccase activity, in contrast, was low at the beginning of incubation but after 6 months it increased signiﬁcantly. The increase of laccase activity was correlated to an increase in fungal biomass, probably reﬂecting a major shift in the litter microbial community. As concerns quality changes, N and lignin content did not signiﬁcantly change during decay. The cellulosic component started being degraded after about 6 months in the litter incubated in two of the three wood sites and from the start of decomposition in the third site. Apart from minor differences in the levels of certain enzyme activities, the data showed that the functional microbial succession involved in the decomposition of Q. ilex leaf litter did not change appreciably in response to differences in soil and microclimatic conditions in the incubation sites.
Keywords: Cellulose; Enzyme activities; Fungal biomass; Lignin; litter decomposition; Microbial respiration

Decomposition dynamics of Myrtus communis and Quercus ilex leaf litter: Mass loss, microbial activity and quality change - Fioretto, A.; Papa, S.; Pellegrino, A.; Fuggi, A. (Applied Soil Ecology, 2007)
The patterns of microbial respiration and enzyme activity (cellulase, xylanase, laccase and peroxidase) in the leaf litter of two evergreen sclerophyll species, Myrtus communis and Quercus ilex, were compared during decay in a low shrubland and in a coppice wood in a Natural Reserve in the Mediterranean area. The two litter types had similar initial amounts of lignin, cellulose and acid-detergentsoluble substances, but the litter from M. communis had a lower N content and higher C/N ratio. In spite of this, the decomposition rate of M. communis litter was higher than for Q. ilex. Whilst no seasonal variation was observed in the rate of organic matter degradation, respiration and extractable cellulase and xylanase activities showed seasonal variation in both litter types with the highest values in winter–early spring and the lowest in summer, and showed positive correlations with water content. Peroxidase activity exhibited a seasonal pattern and was higher in Q. ilex than in M. communis, while laccase activity was higher in M. communis and increased with fungal biomass as degradation progressed. Nevertheless, no relationship was found between laccase and peroxidase activity and lignin degradation. The results obtained indicate that the seasonal alternation of moist and dry periods is the major factor inﬂuencing soil biological activity in the Mediterranean area. The occurrence of pronounced seasonal variation in litter enzyme activity prevents the determination of possible correlations with litter mass loss.
Keywords: Cellulose; Enzyme activity; Fungal biomass; Lignin; litter decomposition; Microbial respiration

Decomposition dynamics of Myrtus communis and Quercus ilex leaf litter: Mass loss, microbial activity and quality change - Fioretto, a; Papa, S; Pellegrino, a; Fuggi, A (Applied Soil Ecology, 2007)
The patterns of microbial respiration and enzyme activity (cellulase, xylanase, laccase and peroxidase) in the leaf litter of two evergreen sclerophyll species, Myrtus communis and Quercus ilex, were compared during decay in a low shrubland and in a coppice wood in a Natural Reserve in the Mediterranean area. The two litter types had similar initial amounts of lignin, cellulose and acid-detergentsoluble substances, but the litter from M. communis had a lower N content and higher C/N ratio. In spite of this, the decomposition rate of M. communis litter was higher than for Q. ilex. Whilst no seasonal variation was observed in the rate of organic matter degradation, respiration and extractable cellulase and xylanase activities showed seasonal variation in both litter types with the highest values in winter–early spring and the lowest in summer, and showed positive correlations with water content. Peroxidase activity exhibited a seasonal pattern and was higher in Q. ilex than in M. communis, while laccase activity was higher in M. communis and increased with fungal biomass as degradation progressed. Nevertheless, no relationship was found between laccase and peroxidase activity and lignin degradation. The results obtained indicate that the seasonal alternation of moist and dry periods is the major factor inﬂuencing soil biological activity in the Mediterranean area. The occurrence of pronounced seasonal variation in litter enzyme activity prevents the determination of possible correlations with litter mass loss.
Keywords: Cellulose; Enzyme activity; Fungal biomass; Lignin; litter decomposition; Microbial respiration

Lignin and cellulose degradation and nitrogen dynamics during decomposition of three leaf litter species in a Mediterranean ecosystem - Fioretto, Antonietta; Di Nardo, Carmelina; Papa, Stefania; Fuggi, Amodio (Soil Biology and Biochemistry, 2005)
Cellulose and lignin degradation dynamics was monitored during the leaf litter decomposition of three typical species of the Mediterranean area, Cistus incanus L., Myrtus communis L. and Quercus ilex L., using the litter bag method. Total N and its distribution among lignin, cellulose and acid–detergent–soluble fractions were measured and related to the overall decay process. The litter organic substance of Cistus and Myrtus decomposed more rapidly than that of Quercus. The decay constants were 0.47 yearK1 , 0.75 yearK1 and 0.30 yearK1 for Cistus, Myrtus and Quercus, respectively. Lignin and cellulose contents were different as were their relative amounts (34 and 18%, 15 and 37%, 37 and 39% of the overall litter organic matter before exposure, for Cistus, Myrtus and Quercus, respectively). Lignin began to decrease after 6 and 8 months of exposure in Cistus and Myrtus, respectively, while it did not change signiﬁcantly during the entire study period in Quercus. The holocellulose, in contrast, began to decompose in Cistus after 1 year, while in Quercus and Myrtus immediately. Nitrogen was strongly immobilized in all the litters in the early period of decay. Its release began after the ﬁrst year in Cistus and Myrtus and after 2 years of decomposition in Quercus. These litters still contained about 60, 20 and 90% of the initial nitrogen at the end of the experiment (3 years). Prior to litter exposure nitrogen associated with the lignin fraction was 65, 54 and 37% in Cistus, Myrtus and Quercus, while that associated with the cellulose fraction was 30, 24 and 28%. Although most of the nitrogen was not lost from litters, its distribution among the litter components changed signiﬁcantly during decomposition. In Cistus and Myrtus the nitrogen associated with lignin began to decrease just 4 months after exposure. In Quercus this process was slowed and after 3 years of decomposition 8% of the nitrogen remained associated with lignin or lignin-like substances. The nitrogen associated with cellulose or cellulose-like substances, in contrast, began to decrease from the beginning of cellulose decomposition in all three species. At the end of the study period most of the nitrogen was not associated to the lignocellulose fraction but to the acid–detergent–soluble substance (87, 88 and 84% of the remaining litter nitrogen).
Keywords: Cellulose; cistus incanus; decomposition dynamics; Lignin; myrtus communis; nitrogen; Quercus ilex

Lignin and cellulose degradation and nitrogen dynamics during decomposition of three leaf litter species in a Mediterranean ecosystem - Fioretto, Antonietta; Di Nardo, Carmelina; Papa, Stefania; Fuggi, Amodio (Soil Biology and Biochemistry, 2005)
Cellulose and lignin degradation dynamics was monitored during the leaf litter decomposition of three typical species of the Mediterranean area, Cistus incanus L., Myrtus communis L. and Quercus ilex L., using the litter bag method. Total N and its distribution among lignin, cellulose and acid–detergent–soluble fractions were measured and related to the overall decay process. The litter organic substance of Cistus and Myrtus decomposed more rapidly than that of Quercus. The decay constants were 0.47 yearK1 , 0.75 yearK1 and 0.30 yearK1 for Cistus, Myrtus and Quercus, respectively. Lignin and cellulose contents were different as were their relative amounts (34 and 18%, 15 and 37%, 37 and 39% of the overall litter organic matter before exposure, for Cistus, Myrtus and Quercus, respectively). Lignin began to decrease after 6 and 8 months of exposure in Cistus and Myrtus, respectively, while it did not change signiﬁcantly during the entire study period in Quercus. The holocellulose, in contrast, began to decompose in Cistus after 1 year, while in Quercus and Myrtus immediately. Nitrogen was strongly immobilized in all the litters in the early period of decay. Its release began after the ﬁrst year in Cistus and Myrtus and after 2 years of decomposition in Quercus. These litters still contained about 60, 20 and 90% of the initial nitrogen at the end of the experiment (3 years). Prior to litter exposure nitrogen associated with the lignin fraction was 65, 54 and 37% in Cistus, Myrtus and Quercus, while that associated with the cellulose fraction was 30, 24 and 28%. Although most of the nitrogen was not lost from litters, its distribution among the litter components changed signiﬁcantly during decomposition. In Cistus and Myrtus the nitrogen associated with lignin began to decrease just 4 months after exposure. In Quercus this process was slowed and after 3 years of decomposition 8% of the nitrogen remained associated with lignin or lignin-like substances. The nitrogen associated with cellulose or cellulose-like substances, in contrast, began to decrease from the beginning of cellulose decomposition in all three species. At the end of the study period most of the nitrogen was not associated to the lignocellulose fraction but to the acid–detergent–soluble substance (87, 88 and 84% of the remaining litter nitrogen).
Keywords: Cellulose; cistus incanus; decomposition dynamics; Lignin; myrtus communis; nitrogen; Quercus ilex

Measurement and characterization of cellulase activity in sclerophyllous forest litter. - Criquet, Stéven (Journal of microbiological methods, 2002)
Cellulases are enzymatic proteins which hydrolyze cellulose polymers to smaller oligosaccharides, cellobiose and glucose. They consist in three major types of enzymes: endoglucanases (EC 3.2.1.4), cellobiohydrolases (EC 3.2.1.91) and beta-glucosidases (EC 3.2.1.21) which play an essential role in carbon turnover of forest ecosystem. The aim of this study was firstly to determine the parameters (i.e. buffer type, pH, temperature, quantity of litter, incubation time and reagent type) which affect the measurement of cellulase activity in a sclerophyllous forest litter, and secondly to compare two methods for measuring cellulase activity: a direct method and an extraction method. In the direct method, the litter was directly incubated with a buffered solution containing the enzyme substrate, whereas in the extraction method, the cellulases were firstly extracted before measuring their activity. The results were compared with other studies about soil cellulase activity, and it appeared that several parameters (buffer type, pH, temperature and sample quantity) which influence the measurement of cellulase activity differ according to whether a soil or a litter is considered. Concerning the procedure used for the measurement of cellulase activity, results showed that the activity values were higher when using an extraction procedure than when using a direct procedure. The extraction procedure, combined with a concentration stage of the extract, also allowed electrophoretic analysis (PAGE) of the cellulases extracted from the litter. The electrophoretic pattern revealed two cellulase isoenzymes which may be related to the occurrence of two pH-activity peaks of these enzymes when citrate buffer was used for the measurement of cellulase activity in the litter.
The following values have no corresponding Zotero field: accession-num: 11997167
Keywords: Buffers; Cellulase; Cellulase: analysis; Cellulase: isolation & purification; Cellulose; Cellulose: metabolism; Endoglucanase; Extraction; Hydrogen-Ion Concentration; Isoenzyme; Isoenzymes; Isoenzymes: analysis; litter; Plant Leaves; Plant Leaves: enzymology; Quercus; Quercus: enzymology; Temperature; Trees

Measurement and characterization of cellulase activity in sclerophyllous forest litter. - Criquet, Stéven (Journal of microbiological methods, 2002)
Cellulases are enzymatic proteins which hydrolyze cellulose polymers to smaller oligosaccharides, cellobiose and glucose. They consist in three major types of enzymes: endoglucanases (EC 3.2.1.4), cellobiohydrolases (EC 3.2.1.91) and beta-glucosidases (EC 3.2.1.21) which play an essential role in carbon turnover of forest ecosystem. The aim of this study was firstly to determine the parameters (i.e. buffer type, pH, temperature, quantity of litter, incubation time and reagent type) which affect the measurement of cellulase activity in a sclerophyllous forest litter, and secondly to compare two methods for measuring cellulase activity: a direct method and an extraction method. In the direct method, the litter was directly incubated with a buffered solution containing the enzyme substrate, whereas in the extraction method, the cellulases were firstly extracted before measuring their activity. The results were compared with other studies about soil cellulase activity, and it appeared that several parameters (buffer type, pH, temperature and sample quantity) which influence the measurement of cellulase activity differ according to whether a soil or a litter is considered. Concerning the procedure used for the measurement of cellulase activity, results showed that the activity values were higher when using an extraction procedure than when using a direct procedure. The extraction procedure, combined with a concentration stage of the extract, also allowed electrophoretic analysis (PAGE) of the cellulases extracted from the litter. The electrophoretic pattern revealed two cellulase isoenzymes which may be related to the occurrence of two pH-activity peaks of these enzymes when citrate buffer was used for the measurement of cellulase activity in the litter.
Keywords: Buffers; Cellulase; Cellulase: analysis; Cellulase: isolation & purification; Cellulose; Cellulose: metabolism; Endoglucanase; Extraction; Hydrogen-Ion Concentration; Isoenzyme; Isoenzymes; Isoenzymes: analysis; litter; Plant Leaves; Plant Leaves: enzymology; Quercus; Quercus: enzymology; Temperature; Trees

Very high-resolution 1H MAS NMR of a natural polymeric material - Gil, A M; Lopes, M H; Pascoal Neto, C; Rocha, J (Solid State Nuclear Magnetic Resonance, 1999)
The use of ultrafast magic angle spinning (>30 kHz) in tandem with delayed echo acquisition is shown to yield very high-resolution 1H MAS NMR spectra of complex natural organic materials. For the first time, very high-resolution 1H MAS NMR spectra are reported for cork and wood components, two natural materials with great economic importance. The effect of the spinning rate on the 1H NMR spectra was evaluated with single-pulse acquisition and delayed-echo acquisition. The delayed-echo acquisition spectra presented linewidths as sharp as 67 and 25 Hz. The narrow peaks, characterised by proton spin–spin and spin–lattice relaxation, were assigned to the isotropic chemical shifts and the general spectral features were shown to correlate with the sample chemical structure. The tentative assignments of cork 1H MAS NMR signals were presented.
Keywords: 1H MAS NMR; Cellulose; Cork; Lignin; Relaxation; suberin

Decomposition of mediterranean leaf litters: A microcosm experiment investigating relationships between decomposition rates and litter quality - Cortez, J; Demard, J M; Bottner, P; Jocteur Monrozier, L (Soil Biology and Biochemistry, 1996)
he decomposition of four mediterranean species leaf litter (Sessile oak, Quercus petraea L.; Holm oak, Quercus ibex L.; Sweet chestnut, Castanea satiua Mill and beech, Fagus syluatica L.) was studied for 90 days under controlled conditions. Respiration and litter mass loss were measured in three types of microcosms: (1) Soil only; (2) Soil + l-y old litter and (3) Soil + l-y old litter + newly senescent litter (freshly fallen). Variations in chemical composition of the litters were determined before and after incubation by the pyroanalysis method. For newly senescent litters decomposition rates per day Kco, (calculated from CO, release) and K, (calculated from mass losses) fitted to the first order exponential decay decreased as follows: sessile oak (Kc,_,, = 0.0043; K, = 0.0049) > holm oak (Km, = 0.0031; K, = 0.0040) = beech (&o~ = 0.0030; K, = 0.0030) > sweet chestnut (Kc% = 0.0001; K,, = non- significant regression); For l-y old litters sweet chestnut (Ko,, = O.oo40, K, = 0.0065) > sessile oak (KEO, = 0.0035; K, = 0.0039) > beech (Kcc,, = 0.0030; K, = non-significant regression). All litters showed a reduction of lipid (mean loss 90.5%), hydrosoluble (mean loss, 54.2%), hemicellulose plus cellulose (mean loss, 40.6%) content and a relative increase of lignin content (mean gain, 34.4%). Among indicators of litter quality (C-to-N ratio, %N, %lignin, lignin-to-N ratio, HLQ), only some of them were correlated with litter decay. The best relationships were established between the decomposition rates (K,) and parameters integrating lignin contents (I = 0.997; n = 3; P < 0.01). The decomposition of l-y old litters fitted well with most of these parameters (0.999 < I < 0.997; n = 3; P < 0.01) in contrast to newly senescent litters
Keywords: Cellulose; decomposition; hemicellulose; leaf litter; Lignin; litter quality (voyant); mass loss; mineralization

Determination of hemicellulose, cellulose and lignin contents of dietary fibre and crude fibre of several seed hulls. Data Comparison - Saura-Calixto, F; Cañellas, J; Garcia-Raso, J (Z Lebensm Unters Forsch, 1983)
The contents of hemicellulose, cellulose and lignin in neutral-detergent fibre, and acid-detergent fibre in hulls of hazelnuts, peanuts, coconuts, sun- flower seeds, p u m p k i n seeds, acorns and chestnuts were determined. Similar cell-wall characteristics for sunflower-acorn, peanut-pumpkin and hazelnut-chest- nut pairs can be deduced from their similar composi- tion. High amounts of hemicellulose and lower ones of cellulose and lignin are dissolved in the process of de- termining crude fibre. The results are discussed.
Keywords: Cellulose; hemicellulose; hulls (PG); Lignin